Determination of the Minimum Alveolar Concentration (MAC) of Isoflurane and Sevoflurane in Callithrix penicillata - Dietze, Wendel; Jorge Ronchi, Samuel; Oliveira Vasques, William; Henrique Hasckel da Silva Pereira, Leonardo; Buoso de Souza, Mônica; Ádson Costa, Ádson; Nunes de Moraes, Aury (Acta Scientiae Veterinariae, 2023)
Background: The minimum alveolar concentration (MAC) is a measure of quantitative anesthetic potency and has become the standard index for the evaluation and comparison of volatile anesthetics, in addition to guiding dose administration. Black-tufted marmosets (Callithrix penicillata) are primates present in the clinical and surgical routine of veterinary hospitals, as well as experimental models, especially in neuroscience. Few studies have evaluated the potency of the main volatile anesthetics in this species. This study aimed to determine the MAC of isoflurane and sevoflurane in C. penicillata using the up-and-down method and to evaluate the effects of these drugs on the quality of anesthetic induction, maintenance, and recovery. Materials, Methods & Results: Twenty-four animals of undetermined age were used. All marmosets were healthy according to hematological and physical evaluation. The animals were randomly divided into 2 groups: ISOMAC and SEVOMAC. Each animal was induced to general anesthesia in an anesthetic box with oxygen (5 L/min) and sevoflurane at 7% in the SEVOMAC group or isoflurane at 5% in the ISOMAC. Upon reaching lateral decubitus, orotracheal intubation was performed. General anesthesia was maintained with isoflurane or sevoflurane diluted in oxygen (0.8 L/min) using a non-rebreathing delivery system under spontaneous ventilation. As defined in the pilot study, the first animal from ISOMAC started the maintenance of anesthesia with 2.6% isoflurane, while the first animal in SEVOMAC received 4% sevoflurane. After finishing the instrumentation to assess heart rate, respiratory rate, systolic blood pressure, pulse oximeter oxygen saturation, end-tidal carbon dioxide concentration, and rectal temperature, a 15-min wait to reach anesthetic equilibrium was allowed, and then an electrical noxious stimulation (50 mA and 50 Hz) was performed on the lateral aspect of the thigh (a faradic current of 3 consecutive single stimuli, followed by 2 continuous stimuli). The animals’ responses to the electrical stimulus were observed. The presence of a positive response (gross movement of the limbs, head, or vocalization) or a negative response (absence of gross movements) determined the increase or reduction, respectively, of the inhalation anesthetic concentration by 10% in the subsequent marmoset. The quality of anesthetic induction and recovery from anesthesia was evaluated using a scale that measured the intensity of agitation, coughing, nausea, and vomiting. Physiological variables were recorded before (M0) and after (M1) applying the nociceptive stimulus. Isoflurane and sevoflurane MAC values in C. penicillata were 2.29 ± 0.10% and 3.93 ± 0.61 % respectively. Physiological parameters, quality of anesthetic induction and recovery did not differ significantly between groups. However, isoflurane caused irritation of the airway and ocular mucous membranes, more coughing episodes, and tearing at induction. There was no difference between groups for time to extubation and recovery time to regain sternal position. Discussion: Previous studies in primates found lower MAC values for both anesthetics, except for Lemur catta. Those findings may be explained by the use of different nociceptive stimuli and the MAC determination method employed, although no differences in MAC values have been described between bracketing or up-and-down methods in human primates and dogs. It is unlikely that the stimulus and technique alone are the determining factors for the high concentration of isoflurane and sevoflurane observed in the present study since MAC was high with both halogenates, indicating that dose extrapolation from other species can lead to the wrong anesthetic dosage. Keywords: Callithrix penicillata, marmoset, isoflurane, sevoflurane, minimum alveolar concentration (MAC).